Alpha-tubulin acetyltransferase/MEC-17 regulates cancer cell migration and invasion through epithelial–mesenchymal transition suppression and cell polarity disruption. Issue 1 (December 2018) - Lee, Cheng-Che; Cheng, Yun-Ching; Chang, Chi-Yen; Lin, Chi-Min; Chang, Jang-Yang
Abstract MEC-17, a newly identified alpha-tubulin-N-acetyltransferase 1, serves as the major α-tubulin acetyltransferase to promote α-tubulin acetylationin vitro andin vivo . Alteration of α-tubulin acetylation may be involved in morphology regulation, cell migration, and tumour metastasis. However, MEC-17's role in cell physiology and its effect on epithelial–mesenchymal transition (EMT) and cell polarity remain elusive. In the present study, we characterized the overexpressed or downregulated cell models through gene targeting as MEC-17 gain- or loss-of-function. Overexpression of MEC-17 enhanced the cell spreading area, suppressed pseudopods formation in a three-dimensional (3D) culture system, and inhibited cancer cell migratory and invasive ability and tumour metastasis by orthotopic lung cancer animal model. Furthermore, morphological change and migration inhibition of cancer cells were accompanied by EMT repression, Golgi reorientation, and polarity disruption caused by alteration of cdc42 activity via a decrease in Rho-GAP, ARHGAP21. By contrast, a reduction in endogenous MEC-17 accelerated the pseudopods formation and EMT, and facilitated cell migration and invasion. These results demonstrated the crucial role of MEC-17 in the modulation of intrinsic cell morphogenesis, migration, and invasive function through regulation of EMT and cell polarity.